Bioaccumulation indexes of metals in blue crab inhabiting specially protected area Koycegiz Lagoon (Turkey) - GENÇ, TUNCER OKAN; YILMAZ, FEVZI (The Indian Journal of Animal Sciences, 2015)
The paper presents original results concerning individual total metal load (IMBI) values, metal pollution index (MPI) and concentrations of 11 metals (Cd, Cr, Cu, Fe, Mn, Ni, Pb, Zn, As, Hg and Se) in blue crab (Callinectes sapidus Rathbun 1896) inhabiting Köyceðiz Lagoon System Turkey. Total of 60 blue crab samples were caught and investigated monthly between June 2009 and May 2010. Concentrations of trace metals in tissues were measured by ICP-AES. Concentration of Cr, Fe, As and Hg were found higher in spring than other season while Cd, Zn, As, Hg and Se showed highest concentration in hepatopancreas. IMBI values in all tissues were higher on spring and summer. On the other hand IMBI values calculated were higher in shell than other tissues. Result of high IMBI values on spring can explain due to the fact that increasing MPI value of Cd, Pb, Fe and Zn on spring while high IMBI values on summer affected by high MPI value of Cd, Pb and Mn. Cd accumulation on autumn and spring also Pb accumulation on every season in blue crab were found higher than the European Units limits for human consumption in edible parts of the crab samples and posed a risk for human health.